ETHNOMEDICINAL PLANTS USED BY TRIBES OF CHITTOOR DISTRICT OF ANDHRA PRADESH TO CURE MUSCULAR PAIN AND INFLAMMATION - Penchala, Pratap Goli; Husain, *Mohd Kashif; Sudarsanam, G.; Alam, Mokhtar; Khair, Shahidul; Hussain Kazmi, Munawwar (International Journal of Ayurveda and Pharma Research, 2018)
An ethnobotanical survey was carried out to collect the first-hand information on medicinal plants used by the inhabited and traditionally rich tribal communities (Chenchus, Yanadis and Nakkalas) in Chittoor district of Andhra Pradesh (AP) for the treatment of muscular pain and inflammation. The information was gathered by an integrated approach of botanical collections, group discussions and questionnaire. The survey revealed thirty forty (34) ethno-medicinal plants belonging to twenty one (21) angiospermic families specifically used for the preparation of medicinal remedies. The tribal claims on the medicinal plants are listed with Latin name, family, local name, part used, method of preparation, dose and its use in pain and inflammation conditions. The habit of frequently used plant were recorded includes tree species (44 %) followed by herbs (35 %) climbers (12 %), under shrubs (6 %) and shrub (3%). Most frequently utilized plant parts were leaves, followed by root, latex, whole plant, bark, fruits, rhizome and seeds. In this particular study the most dominant family was found to be Euphorbiaceae. The result clearly indicates that people living around Chittoor forest area hold valuable traditional knowledge of the use of medicinal plants for their primary health care need related to muscular injury and inflammation. These plant resources are important component in their local livelihood and to control overexploitation of these resources sustainable management approach and proper conservation strategy for the area is also highly recommended by bringing the involvement of local communities and forest department. More in-depth investigations on these claims through phytochemical and pharmacological parameters are required to explore their activities to deal with the conditions of pain and inflammation.